Developing of Eco-Literacy Learning Model to Enhance Environmental Caring Character - Ismawati, Dwi; Fauziah, Puji Yanti; ., Harun; Fuadi , Debi. S.; Suhardiman , Sani (Journal of Ecohumanism, 2024)
This research aims to develop a family partnership-based ecoliteracy learning model to improve the character of caring for the environment in early childhood in Bengkulu City. The research method used is Research and Development (R&D) with reference to the Borg and Gall model, which involves the stages of needs analysis, model design, expert validation, field trials, model refinement, and implementation. The results of the study show that with an average increase from 55 to 80 in PAUD A, from 58 to 82 in PAUD B, and from 60 to 85 in PAUD C. The collaborative approach applied in learning creates a holistic and enjoyable learning environment for children. This research makes a significant contribution to the development of environmental education in Indonesia and emphasizes the importance of the role of parents and teachers in instilling the character of caring for the environment in the younger generation.